Evidence on the effects of bank competition on firm borrowing and investment - Zarutskie, Rebecca (Journal of Financial Economics, 2006)
This paper presents evidence on the financial and real effects of bank competition using a large panel of privately held firms. I trace the firm-level impact of the Riegle-Neal Interstate Banking and Branching Efficiency Act of 1994, which increased the competitiveness of U.S. banking markets. Following the deregulation, newly formed firms used significantly less external debt, were smaller, and realized higher returns on assets, consistent with their investing less due to greater financial constraints. These effects diminish as firms age, ultimately reversing sign. The differential impact that banking market reforms may have on newer and more established firms is underscored.